A informatização da biblioteca da UFSCar e o impacto causado nos trabalhadores devido a mudanças nas rotinas de trabalho: um estudo de caso. - Rizzo, Sheila Regina (Universidade Federal de São Carlos, 2007)
The work and its organization are suffering continually modifications front to the new requirements from the contemporary society. The insertion of new information and communication technologies in the productive processes directs new studies to better understand the logic behind the transformation process and the work organization. The proposal is to study analytically and qualitatively the transformation of the work generated from the insertion of information and communication technologies in the productive processes, as well as the difficulties experienced by the workers. The focus inside the service sector is realized by the study of the Communitarian Library of the Federal University of Sao Carlos (UFSCar) as organization. By the ethnography descriptive methodology, the analysis is made to identify how the library have changed and continue to modify itself with the introduction of information and communication technologies in its products and services and how the employees have been dealing with the difficulties generated by this process.
Keywords: Trabalho (Organização); Sociedade da informação; Tecnologia da informação e comunicação; Transformação do trabalho; Informatização; Bibliotecas; Organization of the work; Technologies of information and communication; Transformation of the work; Motivation; Analysis ethnography; Society of the information; Workers; Informatization; Library; ENGENHARIAS::ENGENHARIA DE PRODUCAO